Vitamin D status and oxidative stress in diabetes mellitus - Lee, Wee Chee; Mokhtar, Siti Safiah; Munisamy, Seetha; Yahaya, Sahran; Rasool, Aida Hanum Ghulam (Cellular and Molecular Biology, 2018)
Diabetes mellitus is an epidemic that is gaining global concern. Chronic hyperglycemia in diabetes induces the excess production of free radicals. The deleterious effects of excess free radicals are encountered by endogenous antioxidant defense system. Imbalance between free radicals production and antioxidants defense mechanisms leads to a condition known as "oxidative stress”. Diabetes mellitus is associated with augmented oxidative stress that induced micro- and macrovascular complications, which presents a significant risk for cardiovascular events. Low vitamin D levels in the body have also been reported to be associated with the pathogenesis of diabetes and enhanced oxidative stress. The article is to review available literature and summarize the relationship between oxidative stress and vitamin D levels in diabetes. We also review the effects of vitamin D analogs supplementation in improving oxidative stress in diabetics.